Desain dan Analisis Geometri Propellant Grain Configuration pada Roket Padat - Muhammad Ihsan Abyan; Aang Nuryaman; Bagus Hayatul Jihad; Soleh Fajar Junjunan (Jurnal Siger Matematika, 2020)
This article examine mathematical model of propellant grain configuration to obtain the appropriate burning area in sonda rocket. Sonda roket is experimental rocket that created by Pustekroket LAPAN to support research on space sector with altitude as the target of assessment. Burning area for hollow grain, wagon wheel grain, star grain are analysed analytically through mathematical modelling. Than the results are compared by manual calculation using SolidWork. The results show that burning area of three types of grain did not show a significant difference between these two methods.